Implementation of ISAK 35 at the Daarul Fathonah Islamic Boarding School Foundation in Tegalgubug Lor District, Arjawinangun District, Cirebon - Nurhaya Abdul Gani; Muhammad Iqbal (Cirebon International Journal of Economics and Business, 2023)
The financial aspect and recording financial reporting is an important aspect of an entity, whether for profit or non-profit. PSAK 45 has regulated the financial reporting rules of non-profit entities since 1997. Then, on April 11 2019, DSAK IAI issued PPSAK 13 which contained the revocation of PSAK 45 and the issuance of ISAK 35. On January 1 2020, the ISAK 35 guidelines came into effect. This research aims to determine financial management at the Daarul Fathonah Islamic Boarding School Foundation and determine its adaptation to ISAK 35. The findings of this research are that the financial management process at the Daarul Fathonah Islamic Boarding School Foundation is divided into five stages, namely planning, implementation, administration, reporting and accountability. The financial reporting of the Daarul Fathonah Islamic Boarding School Foundation is not fully in accordance with ISAK 35; Of the five ISAK 35 financial reports, only three financial reports have been adapted, namely the financial position report, comprehensive income statement and cash flow report, as well as two ISAK 35 financial reports that have not been adapted, namely the report on changes in net worth. and notes to financial reports, because these two financial reports are not required by law.